Nutritional Status and Non-Diet Associated Factors of Hospitalized Heart-Failure Elderly Patients - Shirin Hosseini; Ali Keshavarz; Ahmad Amin; Majid Maleki; Homan Bakhshandeh Abkenar (Sālmand, 2010)
Objectives: The aim of this study was to assess nutritional status and identify the most significant MNA-items (Mini Nutritional assessment) to accelerate the determination of nutritional risk of heart-failure in elderly patients.